2009
DOI: 10.5194/acp-9-945-2009
|View full text |Cite
|
Sign up to set email alerts
|

Coupling aerosol-cloud-radiative processes in the WRF-Chem model: Investigating the radiative impact of elevated point sources

Abstract: Abstract. The local and regional influence of elevated point sources on summertime aerosol forcing and cloud-aerosol interactions in northeastern North America was investigated using the WRF-Chem community model. The direct effects of aerosols on incoming solar radiation were simulated using existing modules to relate aerosol sizes and chemical composition to aerosol optical properties. Indirect effects were simulated by adding a prognostic treatment of cloud droplet number and adding modules that activate aer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
347
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(374 citation statements)
references
References 65 publications
7
347
0
2
Order By: Relevance
“…In particular, from Earth studies we know that the cloud particle sizes strongly influence the cloud radiative forcing (see e.g. Chapman et al 2009;Kobayashi & Adachi 2009, and references therein), since they change the way cloud particles scatter and absorb incident sunlight and thermal radiation. Given the huge number of free parameters in systems like this, our aim was not to cover the whole parameter space, but rather to explore the information content of, in particular, the degree of polarisation of starlight that is reflected by a planet, and the spectral and phase angle ranges that would provide this information.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, from Earth studies we know that the cloud particle sizes strongly influence the cloud radiative forcing (see e.g. Chapman et al 2009;Kobayashi & Adachi 2009, and references therein), since they change the way cloud particles scatter and absorb incident sunlight and thermal radiation. Given the huge number of free parameters in systems like this, our aim was not to cover the whole parameter space, but rather to explore the information content of, in particular, the degree of polarisation of starlight that is reflected by a planet, and the spectral and phase angle ranges that would provide this information.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Knowing the sizes of cloud particles is important for understanding a cloud's influence on a planetary climate, because it determines how a cloud particle scatters and absorbs incident light and thermal radiation (see e.g. Chapman et al 2009, and references therein). How a particle scatters the light depends in particular on the size parameter, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol optical properties calculated based upon volume approximation (Peckham et al, 2011). The aerosolradiative feedback is simulated through coupling with the Goddard shortwave radiation parameterization using aerosol optical depth, single scattering albedo, and asymmetry factor derived from MOSAIC particulates and Mie theory (Ghan et al, 2001;Fast et al, 2006;Gustafson et al, 2007, Chapman et al, 2009) and the Lin et al microphysics parameterization. The aerosol-cloud interation is simulated through coupling with the Lin et al microphysics parameterization (Gustafson et al, 2007;Chapman et al, 2009) that include prognostic treatments of cloud droplet number and activated (cloudphase) aerosol species, aerosol activation and resuspension (Ghan et al, 2001;Zhang et al, 2002), bulk cloud chemistry (Fahey and Pandis, 2001), and in-cloud and below-cloud wet removal of particulates and trace gases (Easter et al, 2004).…”
Section: Model Setupmentioning
confidence: 99%
“…WRF/chem includes a unified significantly coupled mesoscale meteorology chemistry aerosol radiation model, which represents the state-of-thescience online-coupled models that account for many types of feedbacks (Zhang, 2008). WRF/chem has been used in simulating the effect of elevated sources on aerosol forcing and cloud-aerosol interaction in summertime over northeastern North America (Chapman et al, 2009); the three days of studies revealed a domain-averaged reduction of 5 W/m 2 in the mean daytime incoming solar radiation, and the rainfall was increased by 31%. Another study focused on the chemistry-aerosol-cloud-radiation-climate feedbacks over the continental United States (Zhang et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to an LES that only simulates individual cloud systems, regional climate models are able to simulate the feedbacks between clouds and aspects of the large-scale circulation and its variability reasonably well. Even though regional models do not describe part of the large-scale feedbacks, they may be considered a good optimal compromise (Bangert et al, 2011;Van den Heever and Cotton, 2007;Chapman et al, 2009;Forkel et al, 2015;Yang et al, 2012). A still often applied cloud microphysics parameterization in numerical weather prediction is a bulk one-moment scheme (Kessler, 1969;Lin et al, 1983) which uses the specific masses for different hydrometeor species as prognostic variables.…”
Section: Introductionmentioning
confidence: 99%